2021
DOI: 10.1016/j.celrep.2021.109469
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus basalis stimulation enhances working memory by stabilizing stimulus representations in primate prefrontal cortical activity

Abstract: Highlights d Monkey performance of working memory tasks improves with nucleus basalis (NB) stimulation d Activity of prefrontal neurons increases under NB stimulation d Tuning of neurons becomes broader, making the network more stable d Working memory performance is determined by a stabilityaccuracy tradeoff

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 56 publications
3
37
1
Order By: Relevance
“…During the 15 s pauses, biphasic stimulation can be delivered to one or both hemispheres at intensities up to 0.5 mA, with 100 microsecond phase length, biphasic charge balanced pulses. Good effects of stimulation have been documented at 80 pulses per second during that 15 s period ( Liu et al., 2017 ; Qi et al., 2021 ). Retract the recording electrodes first from the recording chamber; when task is done then power off and disconnect the stimulator.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 15 s pauses, biphasic stimulation can be delivered to one or both hemispheres at intensities up to 0.5 mA, with 100 microsecond phase length, biphasic charge balanced pulses. Good effects of stimulation have been documented at 80 pulses per second during that 15 s period ( Liu et al., 2017 ; Qi et al., 2021 ). Retract the recording electrodes first from the recording chamber; when task is done then power off and disconnect the stimulator.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Electrodes may be imaged using CT postoperatively to validate placement, but final placement should be verified histologically. We have demonstrated that these stimulation protocols improve working memory performance ( Liu et al., 2017 ; Qi et al., 2021 ), and sustained attention performance ( Liu et al., 2018 ), generate long-term neuroplasticity based effects ( Liu et al., 2017 ), and desynchronize the EEG ( Qi et al., 2021 ). During recording, for a successful stimulation we will expect to see artifacts from recording electrodes during each stimulation pulse.…”
Section: Expected Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous stimulation of the nucleus basalis and recording in downstream target areas such as the prefrontal cortex during execution of cognitive tasks ( Fig. 3 ) have also began to reveal distinct changes in neural activity that improve working memory stability [ 147 ].…”
Section: Cholinergic Dbs Stimulationmentioning
confidence: 99%
“…Investigating the effects of NB stimulation on neuronal activity is essential for understanding its mechanism of action and optimizing its effectiveness ( Subramaniam et al, 2021 ). NB stimulation affects neuronal activity in the prefrontal cortex during performance of working memory tasks ( Qi et al, 2021 ). Reported results generally indicated an increase in mean firing rate of prefrontal neurons; however, the effects were considerably diverse, including a substantial minority of neurons being suppressed by stimulation.…”
Section: Introductionmentioning
confidence: 99%